The reality of educational and psychological care of talented and superior intelligent children in the primary school - charifi, halima (Journal of Social Sciences and Humanities, 2020)
The object of this study is to expose the reality of educational and psychological care of superior intelligent and talented children considering that this category of pupils exists a large numbers in the first years of learning amongtheir educational community. Psychologists and educators stress that they have special needs because educators must provide them with psychological and educational support in order to achieve psychological, academic and social adjustment. In our study, we proceeded to two main questions: -what is the reality of the direct care ( which includes guidelines and educational services that is provided directly to the pupils) of talented pupils in primary school? -what is the reality of indirect care ( experts present guidelines to the teacher without having a direct contact to the pupil) of the talented young learners in primary school? The study was conducted by applying a questionnaire on a group of primary school teachers in Hammam Dhalaa 1 county, wilaya of M'sila, which involved around two essential subjects: direct and indirect care. After presenting, interpreting and discussing the results, it was found that the psychological and educational care of gifted students, whether direct or indirect, is virtually non-existent in primary school. What we have actually seen is only personal initiatives of teachers, who are particularly interested in the cognitive aspect while ignoring the other aspects, so that this aspect does not receive the necessary attention; This is due to the lack of resources and resources, particularly with the intensity of the programs and the density of classrooms for students, making it difficult for teachers to pay special attention to gifted students. And also the teachers have not been trained by experts regarding the method of dealing with this category.